Molecular Function and Regulation of Non-coding RNAs in Multifactorial Diseases - Mohammadreza Hajjari (Frontiers Research Topics, 2016)
Our understanding of the mechanisms underlying the development of multifactorial diseases such as diabetes, autism, Alzheimer's disease, and cancer has been greatly advanced. Non-coding RNAs (ncRNAs), generally including microRNAs and long non-coding RNAs, have recently been found to have potential roles in these diseases, and provide new opportunities for developing both specific biomarkers and therapeutic targets. However, the molecular function and regulation of these RNAs still remains challenging. Numerous studies are focusing on this field in order to fully appreciate the role and regulation of these molecules in human medicine and biology. This e-book aims to bring together new findings on Non-coding RNAs in different complex diseases. It will highlight the characterization, roles, mechanism, and mode of action of these RNAs in complex disorders. We believe that the publications on this topic would be exponentially extended in future. The improved approaches at multiple levels may pave the way for designing and applying new biomarker and therapeutic targets for specific diseases based on these attractive molecules.